The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.26848/rbgf.v12.5.p1703-1712
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição dos fluxos de umidade em evento de precipitação intensa ocorrido no leste do Nordeste do Brasil em maio de 2017: Um estudo de caso (Contribution of moisture flows in heavy rainfall event occurred in eastern Northeast Brazil in May 2017: A case study)

Abstract: A observação de distribuição espacial e temporal do regime de chuvas da região Nordeste do Brasil (NEB) torna-se um desafio devido sua grande variabilidade no tempo e no espaço. No período de 25 a 29 de maio de 2017 foram registrados casos de chuvas intensas na parte leste do NEB, principalmente entre os estados de Alagoas e de Pernambuco. Desta forma, objetivo deste trabalho consistiu em verificar a contribuição dos fluxos de umidade associada ao evento de precipitação severa ocorrido na região leste do NEB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Researchers analyzed the moisture flux of precipitation system events on the NEB east coast and observed that the region is characterized by the convergence of humidity borne by the trade winds, east waves and breezes associated with the topography, in addition to the circulation and the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Researchers analyzed the moisture flux of precipitation system events on the NEB east coast and observed that the region is characterized by the convergence of humidity borne by the trade winds, east waves and breezes associated with the topography, in addition to the circulation and the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 92%
“…the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As suas tmáx variam entre 27 e 33°C, são capitais vizinhas e, que apresentam um decréscimo na tmáx no período de junho a agosto (Figura 3e, f), que coincide com o período chuvoso no leste do NEB. Nesta época do ano, os distúrbios ondulatórios de leste (DOL) são os responsáveis pela formação de aglomerados de nuvens que causam chuvas nesta região (Ferreira e Mello, 2005;Coutinho e Fish, 2007;Correa et al, 2019). Mas também é inverno no Hemisfério Sul que, em geral, há queda nas temperaturas pela maior frequência de sistemas frontais de maio a setembro (Cavalcanti e Kousky 2003;Andrade 2005), que se aproximam pelo sul do NEB e, acabam de certa forma, influenciando a região de forma indireta (Figuras 3e, 3f).…”
Section: Resultsunclassified